Exploring the motivations and repeat behavioral intentions of generation X and Y Chinese cruise tourists. Issue 4 (2nd October 2021) - Pan, Tianyu; Beckman, Eric; Kitterlin-Lynch, Miranda; Zhao, Jinlin; Cheng, Michael
ABSTRACT: This research aims to use an integrated theoretical model to explore the reasons why Chinese generation X and Y travelers cruise, and the resultant repeat behavioral intentions. As more cruise companies acknowledge the potential cruise market that China has to offer, there is great potential value in understanding the motivations for generation X and Y to cruise, and their future intent to cruise again. A mixed methodology was used based on data collected from past cruise travelers from China. The results indicated that motivation and behavioral differences exist within generation groups. Perceived behavioral control significantly affects generation X's behavioral intention, but generation Y is more controlled by their attitude.